Riparian buffers made of mature oil palms have inconsistent impacts on oil palm ecosystems. Issue 4 (29th March 2022) - Pashkevich, Michael D.; Luke, Sarah H.; Aryawan, Anak Agung Ketut; Waters, Helen S.; Caliman, Jean‐Pierre; Dupérré, Nadine; Naim, Mohammad; Potapov, Anton M.; Turner, Edgar C.
Abstract: Expansion of oil palm has caused widespread declines in biodiversity and changes in ecosystem functioning across the tropics. A major driver of these changes is loss of habitat heterogeneity as forests are converted into oil palm plantations. Therefore, one strategy to help support biodiversity and functioning in oil palm is to increase habitat heterogeneity, for instance, by retaining forested buffers around rivers when new plantations are established, or maintaining buffers made of mature oil palms ("mature palm buffers") when old plantations are replanted. While forested buffers are known to benefit oil palm systems, the impacts of mature palm buffers are less certain. In this study, we assessed the benefits of mature palm buffers, which were being passively restored (in this case, meaning that buffers were treated with no herbicides, pesticides, or fertilizers) by sampling environmental conditions and arthropods within buffers and in surrounding non‐buffer areas (i.e., areas that were 25 and 125 m from buffers, and receiving normal business‐as‐usual management) across an 8‐year chronosequence in industrial oil palm plantations (Sumatra, Indonesia). We ask (1) Do environmental conditions and biodiversity differ between buffer and non‐buffer areas? (2) Do buffers affect environmental conditions and biodiversity in adjacent non‐buffer areas (i.e., areas that were 25 m from buffers)? (3) Do buffers become more environmentally complex and biodiverse over time? We found that buffers can have environmental conditions (canopy openness, variation in openness, vegetation height, ground cover, and soil temperature) and levels of arthropod biodiversity (total arthropod abundance and spider abundance in the understory and spider species‐level community composition in all microhabitats) that are different from those in non‐buffer areas, but that these differences are inconsistent across the oil palm commercial life cycle. We also found that buffers might contribute to small increases in vegetation height and changes in ground cover in adjacent non‐buffer areas, but do not increase levels of arthropod biodiversity in these areas. Finally, we found that canopy openness, variation in openness, and ground cover, but no aspects of arthropod biodiversity, change within buffers over time. Collectively, our findings indicate that mature palm buffers that are being passively restored can have greater environmental complexity and higher levels of arthropod biodiversity than non‐buffer areas, particularly in comparison to recently replanted oil palm, but these benefits are not consistent across the crop commercial life cycle. If the goal of maintaining riparian buffers is to consistently increase habitat heterogeneity and improve biodiversity, an alternative to mature palm buffers or a move toward more active restoration of these areas is, therefore, probably required.